Factors influencing the design and implementation of EAP content-based courses for second-language underprepared students at tertiary level : a Southern African perspective. - Kotecha, Piyushi. (My University, 1993)
This study explores the factors which influence the design and implementation of EAP content-based courses for second-language learners at tertiary level. It draws upon international experience in this area, information from a case study of an adjunct EAP, content-based engineering course at the University of the Witwatersrand and the experience of other EAP practitioners in Southern Africa. A set of key ,comprehensive factors which affect the success and effectiveness of EAP content based courses are identified.
A thesis submitted to the Faculty of Education, in fulfillment of the requirements for the degree of Master of Education
Keywords: English language -- Study and teaching (Higher) -- Africa, Southern -- Foreign speakers.; Universities and colleges -- Africa, Southern.